Kay Thompson's Eloise in Paris - Thompson, Kay, 1909-1998 (Simon & Schuster Books for Young Readers, 1999)
The talkative and precocious Eloise visits Paris with her nanny, enjoys it immensely, and learns several French words and phrases. America's favorite enfant terrible turns the City of Lights upside down in this second book in the Eloise series, first published to great acclaim in 1957 and unavailable for 35 years.